The Heroine's/Hero's Journey—A Call for Transformation? Transformative Learning, Archetypal Patterns, and Embodied Knowing/Learning. (April 2022) - Lehner, Daniela
This article explores the phenomena of personal transformation within the frame of a self-experiential workshop, named the Heroine/Hero's Journey. The Heroine/Hero is the archetype who sets out on an adventurous journey, in pursuit of her or his call for transformation. Rebillot based on Campbell's (1949) mythological work, The Hero with a Thousand Faces created an experiential approach in the form of a one-week workshop, which utilizes methods from theatre and Gestalt therapy. This phenomenologically oriented vignette research draws on interviews and co-experienced observations, which were conducted during the workshop in order to explore the participants' experiences and the content of participants' transformation. The embodied representation of personality patterns, conscious and unconscious and especially the confrontation of these patterns, created transformative experiences for the participants. The depth psychological understanding of transformative processes, highlighting the potential of embodied and archetypal ways of knowing, provides the theoretical frame for giving meaning to these experiences.